Minimizing overhead using efficient PUF-based authentication in flying ad hoc networks - Aljbur, Nazik K.; Yousif, Mohammed; Al-Shareeda, Mahmood A.; Almaiah, Mohammed Amin; Obeida, Mansour (International Journal of Innovative Research and Scientific Studies, 2025)
High-mobility and low-computation resource UAVs are the basic units of what are called Flying Ad Hoc Networks (FANETs), which are prone to abuse and subject to wireless threats. Therefore, secure and efficient communication protocols are needed to guarantee the safety of information exchange. Traditional cryptographic solutions are not suitable due to the high resource demands expected from UAV platforms. In order to mitigate this challenge, this paper presents an improved lightweight authentication scheme based on Physically Unclonable Functions (PUFs) with the goal of reducing the communication and computation overhead in FANET systems. The proposed protocol utilizes index-based challenge–response pair (CRP) referencing along with optimized XOR-based session key generation and lightweight hash primitives to provide secure mutual authentication of UAVs and ground stations. It also provides scalability features such as UAV–UAV authentication through the ground station and group-based authentication for swarm UAV deployments. Our security analysis proves the resistance to replay, impersonation, and man-in-the-middle attacks, and performance evaluation shows that our scheme reduces communication overhead by 27% and computational cost by 30% compared to the existing schemes. This enables the proposed protocol to become a real-time and resource-constrained protocol that works with aerial networks.